PEMBERDAYAAN KADER AISYIYAH DESA KARANGNANAS DALAM PEMANFAATAN BUKU KIA UNTUK DETEKSI DINI PENYULIT PERSALINAN - Kurniati, Citra Hadi (Community Services and Social Work Bulletin, 2021)
The Maternal and Child Health Book (KIA) is one of the documentation tools used to detect complications in childbirth early. It is very important for pregnant women to study this Maternal and Child Health Book (KIA) so that if an abnormality occurs, they can immediately contact the nearest health worker. Health cadres are people who are closest to the community and often interact with the community. Cadres often meet with pregnant women, so it is easy to convey things related to pregnancy and the problems faced by pregnant women. The purpose of this paper is to describe the training of Aisiyah cadres and pregnant women in early detection of complications in childbirth through the Maternal and Child Health Book (KIA). Implementation of Activities To solve existing problems can be done with several methods of activities such as lectures, discussions, leaflets, and training. Results There is an increase in knowledge and skills in early detection of complications in childbirth through the Maternal and Child Health Book (KIA). The findings of the study conclude that the Maternal and Child Health Book (KIA) is a documentation tool in early detection of labor.